Model Analisis Kesenjangan di Bidang Manajemen Sumberdaya Manusia - Agus Kuncoro, Dwi (Unisia, 2012)
So far the Gap Analysis have been recognized in the areas of operational and marketing managements, and in fact these are different one and each other, based on their own characteristics. In the area of human resource management there has not been a standardized gap analysis, and therefore, it is necessary to develop one. This article will introduce a gap analysis for human resource management, and will show organization situation as a case study. Keywords: gap analysis, management, organization, human resources